School Effectiveness in Terms of Learners’ Growth and Academic Achievement Amidst Socio-Economic Challenges; A Case of Makululu Day Secondary School, Kabwe District, Zambia - Malaya, Hellen; Roy, Nil Ratan (Future Science / FSH-PH Publications, 2025)
This study investigated the school effectiveness of Makululu Day Secondary School in terms of learners’ growth and academic achievement amidst the socio-economic challenges faced by the school community. It further explored the strategies used by the school to improve the academic achievements and overall growth of the students. A qualitative research method was employed using a case study design. Eight teachers were involved using stratified simple random sampling, and data were collected through semi-structured interviews. The results were thematically analysed and they showed that the effectiveness of Makululu Day Secondary School was factored by good teaching and learning strategies employed by the school, learners’ emotional welfare, and community cooperation.